(3JfXje GdGOGQI GdeGdjI (B:s (3ef CLd JQTjO GdGfaGb GdMchej h ecGaMI GdaSGO (B/s - (3GdhGOj, eMehO MSjfs ((3YeGf(B: s (3OGQ UaGA(B, s, 2009)
(3GdCSS GdMOjKI aj EYOGO GdehGRfI GdYGeI ddOhdI , GdJNWjW GdeGdj GdGSJQGJjLj , GdSjGSGJ GdGbJUGOjI , GdQbGHI GdeGdjI GdYGeI , GdaSGO GdeGdj h GdGOGQj(B.s
(3eQGLY U(B.321 (3;edGMb U(B.299s
Keywords: (3GdGOGQI GdYGeIs; (3GdGOGQI GdeGdjIs; (3GdGfaGb GdMchejs; (3GdMcheIs; (3GdaSGOs